INFLUENCE LITERACY FINANCE, FINANCIAL USE TECHNOLOGY, AND ONLINE SHOPPING HABITS ON MANAGEMENT GENERATION Z FINANCE - Sri Apgusni Sartika Gea; Kalep Silaban; Januardin Manullang; Rintan Br. Saragih (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to analyze the influence of financial literacy, the use of financial technology (fintech), and on line shopping habits on the financial management of Generation Z in the city of Medan. The background of this research is based on the phenomenon of increasing digital financial activities among the younger generation, which is accompanied by challenges in managing finances wisely in the digital era. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire distributed to 400 respondents from Generation Z in Medan City. The analysis technique used was multiple linear regression analysis with the help of SPSS version 26 software. Before regression analysis was carried out, the data were tested using validity, reliability, and classical assumption tests which included normality, multicollinearity, and heteroscedasticity tests. The results of the study show that the three independent variables, namely financial literacy, fintech use, and on line shopping habits, have a positive and significant effect partially or simultaneously on financial management. The variable of online shopping habits has the most dominant influence on financial management with the highest regression coefficient value (0.498). The Adjusted R Square value of 0.478 indicates that 47.8% of the variation in financial management can be explained by these three variables. Thus, it can be concluded that the financial management ability of Generation Z in Medan City is significantly influenced by finance literacy, the use of digital financial technology, and on line consumption behavior that is carried out wisely